Cyber Counseling Berbasis Seni sebagai Penawar Gejala Trauma Dampak Pandemi Covid-19 - Karyanti Karyanti; Dina Fariza Tryani Syarif; Muhammad Andi Setiawan (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
An increasing number of people affected by COVID-19 is likely to lead to increased levels of emotional trauma and mental illness. This article systematically reviews available data on the benefits of interventions to reduce the adverse mental health sequelae of infectious disease outbreaks and offers guidance for mental health services' responses to infectious disease pandemics. Increasing public mental health literacy is very important to prevent a mental health crisis during the COVID-19 pandemic. The purpose of this study was to determine the effectiveness of art-based cyber counseling to reduce symptoms of trauma due to the Covid 19 pandemic. The research method used Literature Review, by collecting data from national and international journal articles. Art-based counseling and cyber counseling interventions are reported to be effective against the mental health impact of COVID-19. Art-based counseling and cyber counseling interventions are reported to be effective against the mental health impact of COVID-19. The art-based cyber counseling service strategy is an effective choice to increase mental health response capacity for current and future infectious diseases. however, the usefulness and limitations of providing cyber health counseling must also be recognized.